Eksperimen Model Pembelajaran Pendidikan Agama Islam di SMP - Soemanto Soemanto (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2011)
AbstractThis experiment research explains that; 1) any difference on the learning process average on Moral between the group applying a Heart Intelligence (experiment) and control group in six districts/cities of the experiments locations; 2) any difference on the learning process average on Faith between the group applying the learning model on Fertilizing the Seeds of Faith (experiment) and the control group; and 3) any significant difference on Learning Ambience, Group Dynamic and Teacher Performance between the experiment and the control groups.Â Â AbstrakPenelitian eksperimen ini menjelaskan bahwa; 1) terdapat perbedaan rerata hasil belajar Akhlak antara kelompok yang menggunakan model pembelajaran Kecerdasan Hati (eksperimen) dengan kelompok kontrol pada enam kabupaten/kota lokasi eksperimen; 2) terdapat perbedaan rerata hasil belajar Aqidah antara kelompok yang menggunakan model pembelajaran Menyuburkan Benih Iman (ekperimen) dengan kelompok kontrol; dan 3) terdapat perbedaan yang signifikan Suasana Belajar, Dinamika Kelompok dan Kinerja Guru antara kelompok eksperimen dan kelompok kontrol.